CHINESE MEDICINAL HERBS IN TREATING MODEL RATS WITH HEPATIC FIBROSIS - Zhou, Yun-Xiao; Chen, Jiu; Li, Jian-Ping; Wang, Yan-Li; Jin, Xiao-Dong (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The objective of this study was to examine the effects of Chinese medicine formula-Yu Zhang Dan (YZD, composed of Herba Lysimachiae, Rhizoma Polygoni Cuspidati, Radix Curcumae) on the model rats with hepatic fibrosis. Forty male Sprague-Dawley (SD) rats were used in the present study, and they were separated randomly into 4 groups: a normal control group (Group A, n=5), a model control (Group B, n=15), a high dose of YZD (Group C, n=10), and a low dose of YZD (Group D, n=10). Hepatic fibrosis in rats was induced by carbon tetrachloride (CCl4). The variation of the serum alanine transaminase (ALT), aspartate aminotransferase (AST), hyaluronate acid (HA), laminin (LN), type â…¢ procollagen peptide (Pâ…¢ NP), L-Glutathione (GSH) was respectively measured with radioimmunoassay (RIA) and detection of transforming growth factor-beta 1 (TGF-Î²1) and smooth muscle alpha actin (Î±-SMA) was conducted with immunohistochemistry. The ALT, AST HA, LN and PIII NP levels in the serum of the model control group were significantly higher than those of the normal control group (P<0.05), and both of the high dose of YZD and low dose of YZD significantly decreased the ALT, AST HA, LN and PIII NP levels of the model rats (P<0.05). The TGF-Î²1 and Î±-SMA levels of the model control group were significantly higher than those of the normal control group (P<0.05), and both of the high dose of YZD and low dose of YZD significantly decreased the TGF-Î²1 levels of the model rats (P<0.05) , and only the high dose of YZD significantly decreased the Î±-SMA levels of the model rats (P<0.05). The expression of TGF-Î²1 and Î±-SMA in the liver tissues of the rats were in the cytoplasm of the cells. It may be through decreasing the ALT, AST, HA, LN and PIII NP levels in the serum of the model rats and decreasing the expression of TGF-Î²1 and Î±-SMA in the liver tissues of the model rats that YZD significantly relieved the hepatic fibrosis.